Compared feeding behavior of the bird Numenius phaeopus (Charadriiformes: Scolopacidae) in its northbound and southbound migrations through Panama (UNED Research Journal, 2022)
Introduction: Mangroves and coastal areas are of vital importance for the conservation of many migratory birds for which they provide food and refuge, including the Eurasian whimbrel, Numenius phaeopus, which stops in Panama in a southbound, and, a few months later, in a northbound migration. Objective: To evaluate the hypothesis that the bird uses different feeding behaviors in the southbound and the northbound migration. Methods: In 2018 we measured the time that the birds spent in exploratory pecking, standing, walking, running, and eating, in April-June, and October-November (3-5 days each month, N=56 birds). Results: In both stops, the birds spend the same mean time in all activities, which are dominated by walking (50% of food-related time). Conclusion: This species allocates its feeding time similarly in both stops at Panama.
Keywords: Shorebirds; migratory birds; animal behavior; ethograms; coastal ecosystems